ChemInform Abstract: Pd‐Catalyzed C3‐Selective Arylation of Pyridines with Phenyl Tosylates. Issue 38 (30th August 2013) - Dai, Fenglin; Gui, Qingwen; Liu, Jidan; Yang, Zhiyong; Chen, Xiang; Guo, Ruqing; Tan, Ze
Abstract While the arylation of methylated pyridines with phenyl tosylates occurs in 3‐position (e.g. Vd), naphthyl tosylates react with 4‐methyl pyridine (IVd) at the methyl group [cf.